2021
DOI: 10.3390/agriculture11080744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Humic Substances on Production Parameters, Immune Status and Gut Microbiota of Laying Hens

Abstract: Despite the fact that humic substances (HS) have been frequently studied in relation to their effects on livestock health, studies on their influence on egg production and quality, immunity, and intestinal microbiota of laying hens are limited. In this study, the influence of 0.5% HS supplementation on the specific production parameters of eggshell mineral quality, immune parameters (relative expression of IgA, IGF-2, MUC-2 gene in cecum; activity of phagocytes, percentage of selected lymphocyte subpopulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In Chinese traditional medicine, HAs have been called “WU-JIN-SAN” (乌金散) since 1786 (Miao et al, 2018 ). HAs provide molecules with antibacterial, anti-inflammatory, antioxidant, and immunomodulatory functions (Mudronová et al, 2021 ). Moreover, HAs have been used to treat various diseases, including diarrhea, gastritis, gastric ulcers, and colitis (Rusliandi et al, 2020 ; Socol, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese traditional medicine, HAs have been called “WU-JIN-SAN” (乌金散) since 1786 (Miao et al, 2018 ). HAs provide molecules with antibacterial, anti-inflammatory, antioxidant, and immunomodulatory functions (Mudronová et al, 2021 ). Moreover, HAs have been used to treat various diseases, including diarrhea, gastritis, gastric ulcers, and colitis (Rusliandi et al, 2020 ; Socol, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many beneficial effects of humic substances and fermented products have been monitored in selected parameters and confirmed in many studies [ 32 , 33 , 34 , 35 , 37 , 38 , 42 ]. In terms of parameters such as immunostimulation, a positive effect on the intestinal microbiota, influence on fatty acid composition, improvement of the oxidative stability of meat, and stimulating effect on cellular immunity, without a negative effect on haematological and biochemical parameters, were recorded as significant positive effects.…”
Section: Resultsmentioning
confidence: 89%
“…Supplements of the individual groups of chickens: (1) Experimental group H—experimental group H was fed commercial feed BR1, BR2 and BR3 supplemented with 0.7% of humic substances (HumacNatur AFM, Humacs.r.o., Košice, Slovakia) from the first day of fattening; (2) Experimental group F—chickens in experimental group F were fed commercial feed BR1, BR2 and BR3 supplemented with fermented products at aconcentration of 10% from the 11th day of fattening (fermented products consisted of 50% wheat bran fermented using the strain Cunninghamella elegans CCF2591 and 50% of corn feed fermented using the strain Mortierellaalpina CCF2861); (3) Experimental group FH—chickens in experimental group FH were fed commercial feed BR1, BR2 and BR3 supplemented with a combination of humic substances at aconcentration of 0.7% (from the first day of fattening) and fermented products at a concentration of 10% (from the 11th day of fattening); and (4) Control group C—chickens were fed commercial feed BR1, BR2 and BR3 without any supplements. The specific concentrations of the humic substances and fermented products were chosen based on previous studies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diverse structures and functional groups present in humic substances contribute to properties such as colloidal, spectral, electrochemical, and ion exchange, thereby imparting substantial adsorption capacity. Mudronova et al (2020) [12] observed a decrease in enterobacteria and an increase in lactic acid bacteria in broilers supplemented with humic substances, indicating a promotion of beneficial gut microbiota. Showing that humic substances can affect microbial metabolism, influencing carbohydrate and protein metabolism, and contribute to the reduction of pathogenic viruses and bacteria (Rath et al, 2005) [17] .…”
Section: Introductionmentioning
confidence: 98%